1979
DOI: 10.1002/bjs.1800660312
|View full text |Cite
|
Sign up to set email alerts
|

Modified surgical procedures in intestinal tuberculosis

Abstract: The results of modified surgical procedures in intestinal tuberculosis in 79 patients are presented. Special emphasis is laid on the role of limited ileocaecal resection and ileoplasty. These procedures are safe, quick and easy with preservation of functional portions of the bowel. They are of immense value in emergencies in chronically ill and emaciated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 3 publications
1
40
0
1
Order By: Relevance
“…This finding of involvement of slight younger population was also seen in many other studies. 20,21 Present study showed a slight male predominance than females with abdominal tuberculosis and similar results were seen in a study conducted by Rajput MJ et al 21 Although Indian studies have suggested a slight female predominance. 6 The clinical manifestations of abdominal tuberculosis are quite protean.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This finding of involvement of slight younger population was also seen in many other studies. 20,21 Present study showed a slight male predominance than females with abdominal tuberculosis and similar results were seen in a study conducted by Rajput MJ et al 21 Although Indian studies have suggested a slight female predominance. 6 The clinical manifestations of abdominal tuberculosis are quite protean.…”
Section: Discussionsupporting
confidence: 85%
“…Arif Au et al and Rajput MJ et al, observed preexisting pulmonary tuberculosis in 20% and 33.95% of their patients respectively. 20,21 Majority of abdominal tuberculosis cases have been found in patients with HIV. 25 In the present study we aimed to investigate the incidence of abdominal tuberculosis, percentage of acute presentation, to analyse the clinical presentation, diagnostic modalities and role of surgery for abdominal tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple strictures in a segment may require resection and anastomosis. 28,29 Strictures of recent onset that are not very tight may be left alone or dilated through an enterotomy. 28,29 Bypass procedures are not preferred to resections owing to the possibility of future obstructions and malabsorption.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…28,29 Strictures of recent onset that are not very tight may be left alone or dilated through an enterotomy. 28,29 Bypass procedures are not preferred to resections owing to the possibility of future obstructions and malabsorption. 1 All patients with ileocaecal TB must be offered antitubercular chemotherapy.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…This form according to many authors, often responds badly to medical management 7 . The surgical treatment of intestinal TB too has passed through many phases, from the bypass procedures of the pre-antibiotic era to the radical surgeries such as hemicolectomy and wide resection, followed by the more recent and more conservative, modified surgical procedures such as limited ileocecal resection, and stricturoplasties 8 .This study aims at a fresh look into abdominal TB and at a better understanding of its clinical manifestations, diagnostic modalities, management and its complications.…”
Section: Introductionmentioning
confidence: 99%